The effects of internal and external disturbances for the hybrid fuzzy-fuzzy controller applied to IM-drive - Magzoub, M.A. (Institute of Electrical and Electronics Engineers Inc., 2015)
This research represents a study of the effects of internal and external disturbances for the developed hybrid fuzzy-fuzzy controller (HFFC) scheme to gain control over the speed of an induction motor's (IM) variable speed drive (VSD). In case of an induction motor, the fuzzy current amplitude control and fuzzy frequency control are observed in a closed-loop current amplitude input model. A hybrid controller is formed by a combination of both controllers. In order to overcome a drawback of field oriented control (FOC) method, the principle of HFFC is based on a rule to control a speed of a rotor by utilizing a fuzzy frequency controller during the accelerate-decelerate stage. Whereas, a fuzzy stator current magnitude controller is used during a steady-state stage. The two aspects (current and frequency) of FOC are engaged to design a scalar controller. To observe a performance of a controller, a simulation is carried out by means of software, MATLAB/Simulink. Hence, a performance of a controller is observed by conducting a series of tests, and it has been concluded that a controller is more reliable and shows an insensitive behavior towards the parameter variation in the system and motor robustness to load and noise disturbances. Â© 2015 IEEE.